EARNINGS MANAGEMENT AND CARBON EMISSION DISCLOSURE: THE MODERATING EFFECT OF GOVERNANCE MECHANISMS IN INDONESIAN CORPORATIONS - Dewi, Pintari Annisa Sukmanani; Suryaningrum, Diah Hari (Politeknik Negeri Ambon, 2025)
Introduction: This study investigates the influence that profit management has on the disclosure of carbon emissions, with a particular focus on the moderating function that corporate governance measures have. The number of board members, the proportion of independent commissioners, and the number of times the audit committee meets are all examples of these parameters. The research addresses the growing demand for transparency in corporate environmental performance, especially in industries with high environmental impact.Methods: The study uses Moderated Regression Analysis (MRA) on 80 observations collected from Indonesian industrial companies during 2017–2021. Key variables analyzed include earnings management, capital expenditure, and corporate governance indicators. Descriptive statistics were conducted to identify variation, followed by F-tests, T-tests, and R² tests to evaluate the significance and strength of each variable's effect.Results: The analysis reveals that earnings management does not significantly affect carbon emission disclosure, implying a limited influence of financial manipulation on environmental reporting. In contrast, It has been shown that there is a significant positive association between carbon disclosure and capital expenditure. The only element of corporate governance that substantially impacts the link between carbon disclosure and profitability management is the size of the board of directors for the company. Even though the percentage of independent commissioners and the frequency of audit committees do not greatly regulate the situation, they do significantly impact the link between carbon disclosure and capital spending. Based on these facts, the fundamental function of government, rather than its structure alone, is key to improving environmental accountability. Keywords: Earnings Management, Carbon Emission Disclosure, Capital Expenditure, Corporate Governance, and Moderated Regression